Occupational future time perspective and associated factors among older workers in urban communities of Bangkok, Thailand: A cross-sectional study - Natchanok Khampitak; Orawan Prasitsiriphon; Jate Ratanachina (Journal of Public Health and Development, 2026)
Thailand has become a completely aged society in 2024, with a growing proportion of older adults remaining in the workforce. However, evidence on occupational future time perspective (OFTP), which shapes motivation, work engagement, and retirement decisions, remains limited. This study examined OFTP and its subdimensions: Focus on Opportunities (FO); Perceived Remaining Time (RT); and Focus on Limitations (FL), and associated factors among older workers in urban Bangkok. A cross-sectional survey was conducted among 746 adults aged ≥ 50 years in 15 urban communities between January and July 2025. OFTP was measured using the validated Thai OFTP Scale (10 items, Cronbach’s α=0.88). Descriptive statistics, bivariate analysis, and multiple linear regression were applied. Participants’ median age was 59 years; 54.0% were female. The mean OFTP score was 3.10 ± 0.65. Younger age, better perceived health, and absence of chronic disease were positively associated with OFTP. District-level variation was observed, with Pathum Wan residents reporting lower OFTP. Findings suggest that OFTP among older urban workers is shaped by personal, health, and socioeconomic factors. Policies enhancing healthcare access and supportive urban environments are crucial for sustaining productive employment in later life.